Teknologi Augmented Reality: Apakah memiliki pengaruh terhadap peningkatkan minat belajar siswa dalam menyajikan materi pembelajaran? - Raden Firman Nurbudi Prijambodo; Noor Fazariah Handayani; Wajnah Wajnah; Yeni Meylani; Nurul Hikmah; Friska Ledina Situngkir (Journal on Education, 2024)
Augmented Reality (AR) technology has emerged as an innovative solution in the context of education, promising a more engaging and interactive learning experience. This study aims to examine the influence of Augmented Reality technology on enhancing students' interest in learning in presenting learning materials. The literature review method is employed to investigate related findings in relevant literature. The literature analysis reveals that the use of AR in education has successfully increased students' interest in learning through immersive and interactive learning experiences. Factors such as the sophistication of AR technology, ease of use, availability of relevant content, students' natural interest in the subject, and students' learning preferences influence how effectively AR motivates students. The implications of this research highlight the importance of developing engaging AR content, providing training for teachers to integrate AR into the curriculum, and gaining a better understanding of students' learning preferences. This study concludes that AR holds great potential in enhancing students' interest in learning and contributes significantly to the development of innovative education